PENERAPAN SANKSI TERHADAP PENYIMPANGAN PENYIDIK POLRI DALAM MENANGANI PERKARA - Dani Durahman (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
The functionsand tasks ofthe national policeset upby article13of law No.2of 2002onthe police forcethat iskeeping thesecurityand orderof society,enforce the law,and provide protection,shelter, and serviceto the community.Froma series of tasksthat isone of the tasksthe policeenforce the law,police andlaw enforcement agenciesasauthorizedin the processof investigationthatiscentralor "Gates" in terms oflawenforcement,investigatorshavespecialauthoritycomparedto othermembers ofthe national policeasa law enforcementand may becategorizedas organizerof the Statein accordance withthe provisions of article27figuresand explanations oflawNo. 28of 1999about theorganizers ofa country thatis clean and freeofCorruption,CollusionandNepotism, soagainstinvestigatorswho commitperversion andiniquitycan be applied tospecificcriminal sanctionsoutside ofthe Criminal Code (LexSpecialists)i.e.criminal sanctionsfor corruption.In terms ofenforcement of thelawaninvestigatorsuedprofessional andhasa very highdue tointegrityin performingthe task ofinvestigatorsprone/ susceptibleof occurrenceofirregularitiesin the form ofpracticesof corruption,CollusionandNepotism.The condition ofhuman resourcesInvestigatorscurrentlyare stillmany who have notfollowed thevocational educationReserse, actingbased onexperience orhabitis notbased on thelegislationin force, andthe presence ofinterventionsupervisor/ leadershipso thather independencewas stillunquestionable.Irregularitiesare stillcarried out byinvestigatorsinclude:changing thearticle orevidencethatthere has been,to use theevidencetoprivateinterests,favorsin the casewhich is beingdealt with, abuse ofauthority,andwoulddo violence toimposerecognition, directingorinterventionagainst thewitnesses andexpert witnessesin givinginformationand stillthe presence ofthe personinvestigatorswho receivedbribes.Investigatorswho commitperversion andiniquitycan besubject toappropriatedisciplinary actionPPRINo. 2of 2003about disciplinary rulesmembers ofthe national police,the code of ethicsof the professionofsanctionsbased onRegulationNoAssistant.Pol7in 2006 aboutthe code of ethicsof the professionofPolicedansanksicriminalcorruptionin accordance witharticle 1paragraph (1)subc,and article5,article 6,article 11andarticle 12of law No.20of 2001aboutthe eradication ofcriminal acts ofcorruption.Keyword : sanctions,diversion